Decentralization and access to social services in Colombia (2009)
A central claim in favor of decentralization is that it will improve access to public services, but few studies examine this question empirically. This paper explores the effects of decentralization on access to health and education in Colombia. We benefit from an original database that includes over 95% of Colombian municipalities. Our results show that decentralization improved enrollment rates in public schools and access of the poor to public health services. In both sectors, improving access was driven by the financial contributions of local governments. Our theoretical findings imply that local governments with better information about local preferences will concentrate their resources in the areas their voters care about most. The combination of empirical and theoretical results implies that decentralization provides local officials with the information and incentives they need to allocate resources in a manner responsive to voters' needs, and improve the quality of expenditures so as to maximize their impact. The end result is greater usage of local services by citizens.